Counterfactual thinking: the temporal order effect - BYRNE, RUTH MARY JOSEPHINE (My University, 2004)
People often think about how things might have happened differently. Their counterfactual thoughts tend to mentally undo the most recent event in an independent sequence. Consider a game in which two players must each pick the same color card, both red or both black. The first picks black and the second picks red and so they lose. People think, ?If only the second player had picked black.? Our study tested the idea that the ways in which the players could have won provide counterfactual alternatives to the facts. In three experiments, the same set of facts (both players picked black cards), and the same winning conditions (to win in this new game they must pick different color cards) were presented, but the description of the winning conditions varied (e.g., ?if one or the other but not both picks a red card? vs. ?if one or the other but not both picks a black card?). The results showed that the temporal order effect can be produced or reversed by different descriptions. The descriptions make accessible different elements of the winning possibilities. A theory of the mental representations and cognitive processes underlying counterfactual thinking in the temporal order effect is described.
PUBLISHED
Keywords: Psychology